Enantioselective Construction of Vicinal Tetrasubstituted Stereocenters by the Mannich Reaction of Silyl Ketene Imines with Isatin‐Derived Ketimines. Issue 1 (7th November 2014) - Zhao, Jiannan; Fang, Bing; Luo, Weiwei; Hao, Xiaoyu; Liu, Xiaohua; Lin, Lili; Feng, Xiaoming
Abstract: A highly enantioselective Mannich reaction of silyl ketene imines with isatin‐derived ketimines has been realized by using a chiral N, N′ ‐dioxide/Zn II catalyst. A variety of β‐amino nitriles containing congested vicinal tetrasubstituted stereocenters were obtained with excellent outcomes (up to 98 % yield, >19:1 d.r. and 99 %  ee ). Based on the experimental investigations, a possible transition state has been proposed to explain the origin of the asymmetric induction. Abstract : Getting crowded : The title reaction has been realized using a chiral N, N′ ‐dioxide/Zn II complex as the catalyst. A variety of β‐amino nitriles containing congested vicinal tetrasubstituted stereocenters were obtained with excellent outcomes. A possible transition state has been proposed to explain the origin of the asymmetric induction. Boc= tert ‐butoxycarbonyl, TBS= tert ‐butyldimethylsilyl, Tf=trifluoromethanesulfonyl.